1997
DOI: 10.1023/a:1006843418759
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Chronic dermatophytosis was observed in 2276 (10.02%) of 22,692 patients with dermatophytosis during a period of 5.5 years. Males were affected at least 3 times more frequently than females. The age group most commonly affected was between 20 and 40 years of age. Females were affected more between the ages of 30 to 40 years. Tinea cruris and tinea corporis were the most common clinical types and tinea pedis was the least common type observed. The most frequent isolate was Trichophyton rubrum followed by T. men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…Similar findings were noticed in a study by Sentamilselvi. [6] The higher incidence in males could be due to greater physical activity and increased sweating. Among the clinical types, tinea corporis was revealed to be highest (66 cases) followed by 57 cases of tinea cruris.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were noticed in a study by Sentamilselvi. [6] The higher incidence in males could be due to greater physical activity and increased sweating. Among the clinical types, tinea corporis was revealed to be highest (66 cases) followed by 57 cases of tinea cruris.…”
Section: Discussionmentioning
confidence: 99%
“…study and other studies, which have also stated that tinea corporis and tinea cruris are the most common clinical type of dermatophytic infections. [567] In the studies by Sardari et al . [8] and Verma et al .,[9] it has been reported that tinea cruris was the most common clinical type.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ichthyosis, most tinea lesions are ill defined, 9 as noticed in all three cases, so careful clinical examination is mandatory for detection of these lesions. A previous diagnosis of ichthyosis can mislead an experienced dermatologist to fail to diagnose dermatophytosis, due to their similar clinical signs.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there are few and conflicting data regarding predisposing genetic traits in chronic Tp ( Svejgaard et al, 1983 ; Ahmed et al, 1985 ). Although patients with CWD are frequently described in the literature ( Sentamilselvi et al, 1997–1998 ; Vittorio, 1997 ; Gorani et al, 2002 ; Cordeiro et al, 2006 ; Seyfarth et al, 2007 ; Balci and Cetin, 2008 ; Kong et al, 2015 ), it is not yet known why they are unable to mount CMI responses and resolve the infection. Our present findings may provide some clues to this issue.…”
Section: Discussionmentioning
confidence: 99%
“…CARD9 is an adaptor protein downstream to several immune receptors such as dectin-1, dectin-2, and mincle, which recognize fungal structures and are critical for antifungal Th-17 responses ( Lionakis and Holland, 2013 ). On the other hand, there are also frequent reports of patients presenting with recurrent or chronic widespread dermatophytosis (CWD) of the skin which, although not invasive, is difficult to manage ( Sentamilselvi et al, 1997–1998 ; Vittorio, 1997 ; Gorani et al, 2002 ; Cordeiro et al, 2006 ; Seyfarth et al, 2007 ; Balci and Cetin, 2008 ; Kong et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%